Gender stereotypes in agreement processing with role nouns: a study on Russian - Slioussar, Natalia; Antropova, Daria (Frontiers in Psychology, 2025)
The majority of Russian nouns denoting professions and social roles are grammatically masculine. Some of them have feminine pairs, the others do not, but in modern Russian, most nouns in this group can be used to refer to women — either with masculine or with feminine agreement. This option has some interesting limitations that have been extensively discussed in different theoretical approaches (feminine agreement is grammatical only in the nominative; some combinations of feminine and masculine agreement are ungrammatical). However, very few studies are dedicated to processing and acceptability of the sentences with such nouns. To fill this gap, we conducted three experiments: two word-by-word self-paced reading studies and one acceptability judgment study. Following previous studies of role nouns in different languages, we focused on the interaction of grammatical and extralinguistic factors: grammatical gender in attributive and predicative agreement and gender stereotypes associated with different professions and social roles. We revealed a clear preference for masculine agreement both offline (despite the fact that feminine agreement is grammatical) and online, although it was less pronounced for the sentences with stereotypically “female” professions. In general, ungrammatical sentences had the lowest ratings and the longest reading times, although in the sentences with stereotypically “male” professions, feminine agreement was so unexpected that it could slow down reading times more than ungrammaticality. In some other respects, offline and online data showed curious differences: sentences in which the gender of the predicate matches the gender of the attributive adjective were read significantly faster, but did not receive higher ratings.